THE EFFECT OF PROVIDING PHOTOSYNTHESIS BACTERIA DOSES ON THE GROWTH AND PRODUCTION OF RED CHILI VARIETIES (Capsicum annuum L.) - Imelda Sari Harahap; Suryanyo; Wirdah Febrina Siregar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Red chili cultivation still faces the obstacle of low productivity, so more efficient biofertilization innovations are needed, one of which is through the use of photosynthetic bacteria (PSB). This study aims to evaluate the effect of various PSB doses on the growth and production of three red chili varieties and test for their interaction. The study was conducted from May–August 2025 at the UMT Selatan experimental field using a factorial Randomized Block Design (RAK) with two factors, namely PSB dose (0, 5, 10, 15 ml/L) and varieties (Super Baja, Faruq, Ateng), each with three replications. A quantitative approach was used by measuring growth parameters (plant height, leaf area, stem diameter) and production (number of fruits, fruit weight per sample and per plot). The results showed that PSB had a very significant effect on all parameters, with a dose of 15 ml/L producing the highest vegetative growth and production. Variety also had a significant effect, with Super Baja showing the best performance. There was a significant interaction between PSB dose and variety, with the combination of B3V1 producing optimal production. This study concludes that PSB is effective as a biofertilizer to increase red chili productivity, with important implications for the development of environmentally friendly cultivation and agricultural input efficiency.